Pemberdayaan Masyarakat Dusun Desa Jelat dalam Pembuatan Keripik “Tapelur" sebagai Upaya Peningkatan Gizi - Ariani, Dini; Septiani, Hani; Istianah, Euis Tia; Suryani, Nazwa Dia; Nugraha, Tiara Dinda (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are key indicators of a country's level of public health. One of the leading causes of maternal death during pregnancy and childbirth is Chronic Energy Deficiency (CED), which increases the risk of maternal mortality up to 20 times compared to pregnant women with adequate nutrition. In Baregbeg Health Center, Ciamis District, the prevalence of CED remains high, with 75 pregnant women affected in 2024, and a stunting prevalence of 4.75%. This situation is exacerbated by limited public knowledge about CED and stunting, as well as the lack of innovative nutritious food products. Objective: The purpose of this community service was to empower Posyandu cadres and local communities to improve maternal and child nutrition through education on CED and stunting prevention, and by developing an innovative local food product, keripik tapelur (crispy snacks made from tofu, tempeh, and eggs). Method: This public service activity was conducted in Dusun Jelat, Baregbeg Subdistrict, Ciamis Regency, through five stages: problem identification, program planning, implementation, evaluation, and documentation. Activities included educational sessions using e-leaflets and lectures, training for cadres and community members on making keripik tapelur, and evaluation of knowledge improvement and program sustainability. Result: Health education increased participants’ understanding of CED, stunting, and nutritious food processing. The community successfully produced keripik tapelur as a nutritious and practical complementary food. The product was well received and shows potential for further development as a community-based economic activity. Conclusion: Community empowerment through health education and innovative food processing can be an effective strategy to address CED and stunting. The development of keripik tapelur not only improves nutritional intake but also opens up local economic opportunities. This program supports Sustainable Development Goals (SDGs), particularly good health and well-being as well as economic growth.